PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP EFEKTIFITAS KINERJA PEGAWAI PUSKESMAS RAWAT INAP SIDOMULYO BARAT KOTA PEKANBARU - saputra, trio; marlinda, pebriana; sufi, wasiah (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2016)
This study aims to identify and analyze the effect of transformational leadership style of the effectiveness of employee performance in PHC Sidomulyo Pekanbaru, Based on Law No. 23 of 1992 on Health which emphasizes the importance of improving the quality of health services, especially the level community health centers in the form of health care cost and quality, this study used survey method with quantitative approach. Primary data were collected by distributing questionnaires to the entire population of the research sample numbering 50 employees Sidomulyo Pekanbaru City Health Center data analysis using simple linear regression by using SPSS program to see the effect of the independent variable on the dependent variable. The results of data analysis showed there was a positive and significant influence transformational leadership style with health center staff performance effectiveness Sidomulyo western city of Pekanbaru. This is indicated by tcount amounted to 1,750 with p = 0.000 <0.05. note that the value of R2 (Rsquare) amounted to 0,702. This means that the influence of transformational leadership style of the effectiveness of the performance of employees amounted to 70.2% positive and significant effect of transformational leadership style with employee performance demonstrated the effectiveness of leadership style is suitable to be applied in the health centers. The functioning of transformational leadership on improving the effectiveness of performance based leadership efforts to provide motivation to improve performance in working as part of the organization so that employees develop performance by jointly realize the objectives of the organization.